Mathematical Literacy Ability Viewed From Student’s Learning Style Based on Gender Differences on PBL Assistance Project Assessment - Aula, Maulida Fatma Reza; Suyitno, Hardi; Rosyida, Isnaini (Unnes Journal of Mathematics Education Research, 2019)
This research was aimed to know the effectiveness of PBL assistance project assessments on mathematical literacy ability and to describe student’s mathematical literacy ability based on their learning style and gender. The type of research is the mixed method concurrent embedded design. The sample of this study were students of class VII A as the experimental class and VII E as control class. This research was conducted in SMP Negeri 6 Semarang in the academic year of 2017/2018. The result of this study showed that PBL assistance project assessments is effective on mathematical literacy ability. Male students with visual learning styles is able to master communication well, female students with visual learning styles are able to master communication, mathematising, and representation, male students with auditory learning styles are able to master communication, mathematising, reasoning and argument well, female students with auditory learning styles are able to master communication and mathematising, male and female students with kinesthetic learning styles each are able to master communication and mathematising well.